Implementing competency-based medical education: Moving forward. (3rd June 2017) - Frank, Jason R.; Snell, Linda; Englander, Robert; Holmboe, Eric S.
Abstract: For more than 60 years, competency-based education has been proposed as an approach to education in many disciplines. In medical education, interest in CBME has grown dramatically in the last decade. This editorial introduces a series of papers that resulted from summits held in 2013 and 2016 by the International CBME Collaborators, a scholarly network whose members are interested in developing competency-based approaches to preparing the next generation of health professionals. An overview of the papers is given, as well as a summary of landmarks in the conceptual evolution and implementation of CBME. This series follows on a first collection of papers published by the International CBME Collaborators in Medical Teacher in 2010.